O canal de retorno na TV digital e as estratégias para universalização do acesso a Internet - Avelino, Rodolfo da Silva [UNESP] (2014)
This study analyzes the digital inclusion fo citizens in the information society, mainly its viability as a return channel of the Brazilian Digital TV System (SBTVD). It also presents a literature review, concerning the technologies which, today, enable communication between users and the interactive services available through the open Digital TV stations, in the other words, the return channel. The article also analyzes the effectiveness of the National Brazilian Broadband Plan heading the national broadband plans and strategies adopted by other countries like Argentina and the United States. Some international experience from different countries in the development of supply and in the guarantee of universal access to this technology, provided the basis for the analysis, and in the end, in a systematized way, it highlights its characteristics, objectives and its contributions to implementing it in Brazil